The Quagmire of HIV/AIDS Related Issues which Haunt the Church - Ayers, James R. (The Journal of pastoral care, 1995)
Identifies and explores the extreme difficulties of HIV/AIDS realities for the evangelical Christian churches and which tend to stymie effective ministry. Discusses the issues of morality, morbidity, mortality, reality, responsibility; and concludes that the church has fallen short in its mission to HIV/AIDS persons. Claims that this shortfall has created an integrity question in the minds of those whose lives have been touched by this contemporary health crisis.